We need an ambitious early years strategy. (2nd September 2021) - Porter, Rose
Abstract : There is no doubt that the pandemic truly exposed the value of the early years, yet concurrently, exposing the fragility of the sector. This is why Rose Porter explains that the need for an ambitious early years strategy is never more urgent.